Inrush current computations using an optimised analytical hysteresis model. Issue 5 (4th September 2017) - Renhart, Werner; Bíró, Oszkár; Magele, Christian; Preis, Kurt; Rabel, Alexander
Abstract : Purpose: The purpose of this paper is the modelling and estimation of inrush currents while energising power devices under no load conditions. An analytical representation of the nonlinear B-H curve serves for considering the hysteresis behaviour in the numerical model. Design/methodology/approach: The model is implemented into a standard finite element formulation to compute transient problems. Findings: Inrush currents behave like faults in power distribution facilities. Its prior estimation helps to distinguish between operating conditions and faults. Research limitations/implications: The magnetic cores may become extremely magnetised. At such high material saturations, the material characteristics are not measurable accurately. Hence, the results depend on the extrapolation of the B-H curves. Originality/value: The use of first-order reversal curves within the major hysteresis loops helps in a convenient way to estimate peak and shape of the inrush currents.